Plain Radiography May Be Safely Omitted for Selected Major Trauma Patients Undergoing Whole Body CT: Database Study. (15th July 2012) - Hudson, Sarah; Boyle, Adrian; Wiltshire, Stephanie; McGerty, Lisa; Upponi, Sara
Abstract : Introduction . Whole body CT is being used increasingly in the primary survey of major trauma patients. We evaluated whether omitting plain films of the chest and pelvis in the primary survey was safe. We compared the probability of survival of patients and time to CT who had plain X-rays to those who did not. Method . We performed a database study on major trauma patients admitted between 2008 and 2010 using data from Trauma, Audit and Research Network (TARN) and our PACS system. We included adult major trauma patients who has an ISS of greater than 15 and underwent whole body CT. Results . 245 patients were included in the study. 44 (17.9%) did not undergo plain films. The median time to whole body CT from the time of admission was longer (47 minutes) in patients having plain films, than those who did not have plain films performed (30 minutes), P < 0.005 . Mortality was increased in the group who received plain films, 9.5% compared to 4.5%, but this was not statistically significant (P = 0.77 ). Conclusion . We conclude that plain films may be safely omitted during the primary survey of selected major trauma patients.